Exploring Students’ Engagement in English Classes Using SPADA UNPRI Platforms - Fahada, Nazli; Chairunnisa, Chairunnisa (Pusdikra-Publishing.com, 2025)
This study explores the impact of the SPADA UNPRI platform on student engagement in English classes at Universitas Prima Indonesia. The objectives are to analyze the platform’s effectiveness in fostering cognitive, emotional, and behavioral engagement and to identify factors influencing its implementation. This research uses a mixed-methods approach, the research uses a sequential explanatory design, beginning with quantitative data collection through surveys from 100–150 students, followed by qualitative data from interviews and focus group discussions involving 10–15 participants. The findings reveal that SPADA UNPRI significantly enhances cognitive engagement, with 78% of students reporting an improved understanding of English materials. Emotional engagement is also supported, as 65% found quizzes and interactive features motivating. Behavioral engagement is evident, with 72% of students actively participating in forums. However, challenges such as limited internet connectivity and insufficiently structured social interactions were noted. The study recommends enhancing technical infrastructure to ensure equitable access and incorporating more collaborative activities to strengthen relatedness among learners. By addressing these areas, SPADA UNPRI can further its role as an effective tool for improving student engagement and achieving meaningful learning outcomes.